The Relationship Between Halal Knowledge And Perception With The Attitude Of Buying Halal Food In The Consumer Community In Jambi City - Devi Triana*; Elvin Rosalina; Siti Fati Hatussaadah (Riwayat: Educational Journal of History and Humanities, 2023)
Indonesia is a country where the majority of Muslims are very natural if halal food products become an issue that is quite interesting to study. Most people believe in food products from the seller's words and the logo on the packaging of the food product. The problem that then arises is the amount of food, both raw materials and addictive materials, which makes it difficult to determine the halal origin of the ingredients. Along with the development of food technology food genetic engineering requires consumers to be more critical in choosing halal food products. This research aims to determine the relationship between halal knowledge and perception of the attitude toward buying halal food products with a sample population of the consumer community in Jambi City as many as 105 respondents. Design in research is quantitative descriptive with cross sectional approach method and accidental sampling sampling technique. The instrument used is a questionnaire and data analysis using two stages, namely univariate and bivariate. The results of statistical tests show that the p-value value of 0.252 α (0.05) means that there is no significant relationship between knowledge about halal food and buying attitudes. The results of statistical tests show that the p-value value of 0.041 α (0.05) means that there is a significant relationship between halal perception and buying attitude. Respondent's conclusion has a good knowledge of the concept of halal, a positive perception of halal food products, and a positive attitude about buying halal food products.